Assessing the intensity of Late Quaternary humid phases in the Nefud Desert, northern Arabia - Richard Clark‐Wilson; Simon J. Armitage; Ian Candy; Paul S. Breeze; Nick A. Drake; Huw S. Groucutt; Abdullah M. Alsharekh; Faisal Al‐Jibreen; Michael D. Petraglia; David B. Ryves (Journal of Quaternary Science, 2026)
The climate history of the major dryland zones of the world, such as the Saharo–Arabian Desert belt, plays a key role in the dispersal of early humans through these intermittently inhospitable regions. Here, we assess the relative intensity of Late Quaternary humid phases in northern Arabia through lithological, geochemical, palaeoecological and geochronological analysis of three sediment sequences in the Nefud Desert. Two sequences are marl beds that accumulated in perennial, groundwater‐fed lake systems during two distinct humid phases that occurred in MIS 5e and MIS 5a. The third records sediment accumulation within an ephemeral lake system during the terminal Pleistocene/early Holocene. The altitude of the two MIS 5 deposits indicates that the water table must have reached altitudes of >929 m ASL (MIS 5e) and >922 m ASL (MIS 5a). In contrast, the sedimentary characteristics of the early Holocene sequence imply that, during this interval, the water table was